A bibliometric analysis of ICU nurses' experiences and family interactions during death and dying: Insights from Islamic perspectives - Mohamed Ludin, Salizar; Mohd Ali, Noor Azizah (Journal of Islamic, Social, Economics and Development, 2025)
This bibliometric analysis, utilizing 376 articles from Scopus (2005-2024) and employing VOSviewer and Biblioshiny, examines the experiences of Intensive Care Unit nurses and their interactions with families during end-of-life care within Islamic cultural and spiritual contexts. While scholarly interest in spirituality and family involvement in end-of-life care is increasing, research from Islamic-majority nations remains underrepresented. Findings reveal that ICU nurses frequently encounter significant emotional, ethical, and spiritual challenges when supporting dying patients and their families, often lacking adequate training in spiritual care practices and culturally sensitive communication, particularly within Islamic frameworks. The COVID-19 pandemic further amplified these challenges by disrupting established end-of-life practices. This study emphasizes the critical need for context-specific research within Islamic-majority settings and the integration of Islamic bioethics into nursing curricula. Such initiatives are essential to equip nurses with the necessary competencies to deliver holistic, culturally sensitive care, ultimately improving the experiences of patients, families, and healthcare providers alike.